Comparative Metagenomics and Network Analyses Provide Novel Insights Into the Scope and Distribution of β-Lactamase Homologs in the Environment - Gatica, Joao; Jurkevitch, Edouard; Cytryn, Eddie (Frontiers in Microbiology, 2019)
The β-lactams are the largest group of clinically applied antibiotics, and resistance to these is primarily associated with β-lactamases. There is increasing understanding that these enzymes are ubiquitous in natural environments and henceforth, elucidating the global diversity, distribution and mobility of β-lactamase-encoding genes is crucial for holistically understanding resistance to these antibiotics. In this study, we screened 232 shotgun metagenomes from ten different environments against a custom-designed β-lactamase database, and subsequently analyzed β-lactamase homologues with a suite of bioinformatic platforms including cluster and network analyses. Three interrelated β-lactamase clusters encompassed all of the human and bovine feces metagenomes, while β-lactamases from soil, freshwater, glacier, marine and wastewater grouped within a separate “environmental” cluster that displayed high levels of inter-network connectivity. Interestingly, almost no connectivity occurred between the “feces” and “environmental” clusters. We attributed this in part to the divergence in microbial community composition (dominance of Bacteroidetes and Firmicutes vs. Proteobacteria, respectively). The β-lactamase diversity in the “environmental” cluster was significantly higher than in human and bovine feces microbiomes. Several class A, B, C and D β-lactamase homologues (blaCTX-M, blaKPC, blaGES) were ubiquitous in the “environmental” cluster, whereas bovine and human feces metagenomes were dominated by class A (primarily cfxA) β-lactamases. Collectively, this study highlights the ubiquitous presence and broad diversity of β-lactamase gene precursors in non-clinical environments. Furthermore, it suggests that horizontal transfer of β-lactamases to human-associated bacteria may be more plausible from animals than from terrestrial and aquatic microbes, seemingly due to phylogenetic similarities.